Sustainable Finance and ESG: The Impact of Environmental, Social, and Governance Principles Implementation on Corporate Financial Performance and Firm Value - Agung Nugroho; Andini Nurwulandari; E. Hasanudin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines whether environmental, social, and governance (ESG) practices enhance corporate profitability and firm value by reviewing empirical evidence from previous studies. Using a systematic literature review guided by a PRISMA approach, peer-reviewed articles published between 2010 and 2025 and indexed in Scopus and Web of Science were analyzed. The findings indicate that firms adopting ESG practices generally achieve stronger financial performance and higher market valuation, although the strength and direction of the relationship vary across contexts. Five key factors influence these outcomes: the credibility of ESG disclosure, the financial materiality of ESG issues within the industry, governance quality, environmental exposure, and the institutional maturity of the market. The review also highlights that inconsistencies among ESG rating agencies contribute to measurement differences, leading to mixed empirical findings. Drawing on stakeholder and legitimacy theories, the study suggests that effective ESG implementation reduces information asymmetry, lowers financing costs, strengthens corporate reputation, and increases investor confidence. An integrative framework is proposed to explain the relationship between ESG implementation and firm value while identifying future research opportunities, particularly in emerging economies such as Indonesia, where sustainable finance regulations continue to develop.